Analisis Korelasi Kondisi Pembuatan Film Tipis Polipropilen (PP) dan Sifat-Sifat Mekaniknya Dengan Metode Uji Tarik - Kartika Sari; Rahmat Satoto (BERKALA FISIKA, 2012)
Condition Correlation Analysis of Thin Film Polypropylene (PP) and Attributes Mechanical Tensile Testing Method has been performed in Polymer Test Lab located at LIPI Bandung. This study aims to examine the relationship between the manufacture of thin film with a three-siftat sisitem cooling and mechanical properties. Sample material used is Polypropylene (PP) Y101XX grain pellets. Then the material is arranged on the aluminum frame of the heating plate and plastic transparencies of six samples. Such materials will be heated with two variations of temperature at the same time given the pressure by using the hot press Gonno-02 326 at 175oC and 225oC and given three different treatment when the cooling process that is in the chill with ice water (quenching), in the chill on cold press and cooled until it reaches room temperature by turning off the heater. Samples that have formed a thin film forming dipotopng Dumbbell type ISO 527-2. Of the six films produced by two samples with different cooling systems made seven Dumbbell. Then Dumbbell-dumbbell was conducted testing of mechanical properties by measuring the strain, stress and elastic modulus using a tensile test using a Universal Tensile Tester.   Keywords: Polypropylene (PP), Thin Film, Universal Tensile Tester